Analisis Pengaruh Pendidikan, Kesehatan, dan Ekonomi terhadap Kemiskinan di Kawasan Tapal Kuda Jawa Timur - Siti Halimatuz Zahra; Mohammad Wahed (Commodities, Journal of Economic and Business, 2026)
Poverty is one of the development challenges in the Tapal Kuda region of East Java. This study aims to identify how variables such as education, health, and the economy impact poverty in the Tapal Kuda region. A quantitative approach was employed in this research. Panel data covering the period from 2019 to 2023 were collected from seven regencies, utilizing information from official sources and Statistics Indonesia (BPS). The analysis revealed that the Fixed Effects Model (FEM) with robust standard errors was the most effective approach. The findings indicate that Expected Years of Schooling (HLS), Mean Years of Schooling (RLS), and Life Expectancy (AHH) have a significant negative impact on poverty levels. Conversely, BPJS PBI (subsidized health insurance), Gross Regional Domestic Product (GRDP) per capita, and the Regency/City Minimum Wage (UMK) do not significantly influence poverty. The results suggest that improving the quality of education and health, as well as access to basic infrastructure, is more efficient than relying on economic growth to alleviate poverty. This study is expected to assist local governments in formulating more integrated and targeted poverty alleviation policies.